The nonviolent God - Weaver, John Denny 1941- (Grand Rapids Wm. B. Eerdmans Publishing Co, 2013)
Cover Page -- Title Page -- Copyright Page -- Dedication -- Contents -- Preface -- Introduction -- Part I: The God of Jesus -- 1. Jesus In Acts and the Gospels -- The Earliest Statements: Acts -- Expanded Statements: The Gospels -- The Significance of the Resurrection -- Narrative Christus Victor: Round One -- The Story As Atonement Motif -- Characteristics of Narrative Christus Victor -- 2. Jesus In Revelation and Paul -- Revelation -- Reading Revelation -- The Message of Revelation -- The Seven Seals -- Beautiful Woman Versus Dragon -- Preliminary Conclusion -- Wrath, Judgment, and Divine Violence -- The Rider On the White Horse and Armageddon -- Millennium and Great White Throne -- Narrative Christus Victor: Round Two -- Narrative Christus Victor: Round Three -- The Writings of Paul -- Jesus' Death As a Sacrifice -- 3. Engaging the Atonement Tradition -- Traditional Atonement Images -- From Narrative Christus Victor to Satisfaction Atonement -- The Demise of Narrative Christus Victor -- Resurrection to Death: The Emergence of Satisfaction -- Responding to Challenges -- The Challenge of Paul -- The Challenge of Newness -- The Challenges of Threefold Synthesis and of Keeping One Version But Not Another -- The Challenge of Guilt -- 4. Divine Violence: Bible Versus Bible -- Biblical Violence and Divine Violence -- Divine Violence: Old Testament -- Divine Violence: The Gospels -- Divine Violence: Today's Version -- The Bible: Another Look -- The Old Testament -- Counters to Gospel Violence -- 5. The Conversation About God -- God Versus God -- An Arbiter: The Narrative of Jesus -- The Authority of the Bible -- Anger, Wrath, and Judgment -- Why It Matters -- Part II: The Reign of God Made Visible -- 6. Christology and the Body of Christ -- Five New Testament Christologies -- Nicea-Constantinople, Cappadocian Trinity, Chalcedon
Conversation On Christology -- Lived Christology Today -- The Church As the Lived Narrative of Jesus -- Baptism: Creation of a New World -- The Church: A Community -- A Voluntary Church -- A Peace Church -- 7. Violence and Nonviolence -- The Nonviolence of Lived Theology -- God In the Image of Humankind -- Jesus' Nonviolence -- Nonviolence Applied -- 8. Atonement, Violence, and Forgiveness -- Forgiveness In Narrative Christus Victor -- Forgiveness In Satisfaction Atonement -- The Practice of Forgiveness: Retributive Justice -- The Practice of Forgiveness: Psychology -- The Practice of Forgiveness: Restorative Justice -- 9. Race, Gender, Money -- Jesus and Racial and Ethnic Reconciliation -- Jesus and Women -- Jesus and Economics -- A Warning: The Unholy Troika -- The Lord's Supper: An Economic Model -- Baptism and Lord's Supper As "Sacraments" -- 10. Nature and Suffering -- Jesus and Nature -- Two Kinds of Suffering -- Conclusion -- The Reign of God Today -- Trinity -- The New Jerusalem -- Version One -- Version Two -- Works Cited -- Index
Keywords: Nonviolence - Religious aspects - Christianity; Atonement; Electronic books; Jesus Christ; Nonviolence ; Religious aspects ; Christianity; Bible ; New Testament ; Criticism, interpretation, etc